A FEM Flow Impact Acoustic Model Applied to Rapid Computation of Ocean-Acoustic Remote Sensing in Mesoscale Eddy Seas - Yi Liu; Jian Xu; Kangkang Jin; Rui Feng; Luochuan Xu; Linglong Chen; Dan Chen; Jiyao Qiao (Remote Sensing, 2024)
Mesoscale eddies have an impact on the marine environment mainly in two areas, namely, currents and changes in the sound velocity gradient due to temperature and salt stirring. The traditional underwater-related remote sensing acoustic remote sensing model is capable of analyzing the acoustic field under the change in sound velocity gradient, but it is not capable of analyzing the acoustic field under the influence of ocean currents. In order to more effectively analyze the changes in the acoustic field caused by mesoscale eddies, this paper proposes a FEM flow impact model applied to the rapid computation of acoustic remote sensing of mesoscale eddies in the sea area. The algorithm first performs a grid optimization of the sea area model based on vertical sound velocity variations and completes the classification of sound velocity layer junctions. At the same time, we construct the sound velocity gradient environment affected by the mesoscale eddy and then simplify the fluid flow in the mesoscale eddy into a non-viscous and non-rotating velocity potential, and then participate in the solution of the three-dimensional spatial fluctuation equations in the form of time-harmonic in the frequency domain, from which we can obtain the truncated sound pressure as well as the propagation loss, and quickly and completely characterize the acoustic remote sensing of the sea area of the mesoscale eddy. The paper verifies the effectiveness of the algorithm through SW06-contained flow experiments and further proposes an optimization formula for sound velocity inversion. We analyze this using measured data of mesoscale eddy fields in the Bering Sea waters during 2022 and find that eddies have a greater effect on the propagation of the acoustic field along their flow direction.